HPV associated diseases and women's quality of life - E G Sycheva; N M Nazarova; V N Prilepskaya; O V Bourmenskaya; V E Frankevich (IP Berlin A.V., 2016)
Human papillomavirus is likely the most common sexually transmitted viral infection worldwide. HPV provokes anogenital diseases and genital warts. It should be noted the specific importance of the quality of life assessment of the women with human papillomavirus - associated cervical diseases.